The polyphonic hymns of Valentin Triller’s 'Ein Schlesich singebüchlein' (Wrocław 1555), ed. Antonio Chemotti, Warsaw 2019 - Desmet, Marc (Muzyka, 2020)
Recenzja książki: The polyphonic hymns of Valentin Triller’s 'Ein Schlesich singebüchlein' (Wrocław 1555), wyd. Antonio Chemotti, Warsaw 2019